Imported Plasmodium vivax malaria complicated by reversible myocarditis - Fahmi Y Khan (Wolters Kluwer Medknow Publications, 2019)
Myocarditis as a result of malaria infection is uncommon. However, we report a case of a Pakistani emigrant who presented with respiratory distress, fever, chills, and nausea at the emergency room. The patient had traveled to visit his relatives in Pakistan without receiving antimalarial chemoprophylaxis. (Travel clinic advises travelers to Pakistan to take antimalarial drugs as prophylaxis.) Cardiorespiratory examination revealed bilateral crepitation in all lung fields, as well as triple heart sounds. Examination of blood smear showed trophozoites and schizonts of Plasmodium vivax with low parasite density. Echocardiography showed diffuse hypokinesia with an ejection fraction of 22% consistent with acute myocarditis. The patient was given chloroquine phosphate, digoxin, perindopril arginine, furosemide, and spironolactone and gradually improved.